2021
DOI: 10.1016/j.ypmed.2020.106323
|View full text |Cite
|
Sign up to set email alerts
|

Cognitions and behaviours of general practitioners in France regarding HPV vaccination: A theory-based systematic review

Abstract: Human papillomavirus (HPV) vaccination is safe and efficacious to prevent persistent HPV infection, precancerous anogenital lesions and cervical cancer. However, in countries where vaccination programmes are implemented outside of schools, such as France, reaching high HPV vaccination coverage of the target population is challenging. Many studies have been performed in France to assess cognitions of general practitioners (GPs) regarding HPV vaccination. However, the evidence is not consistent about which cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…A message that targeted the fundamental motive of kin care significantly improved mothers’ attitudes toward HPV vaccination and significantly increased mothers’ intention to have their daughter(s) receive the HPV vaccine compared to a control message. Previous research and practice on behavior change, including vaccination recommendations, have been based mainly on cognitive behavioral models, and focused on cognitive beliefs such as perceived susceptibility and severity of infection [ 9 , 10 ]. Previous studies have shown that many vaccine recommendation messages target the fundamental motive of disease avoidance and communicate the causes of infectious diseases and the benefits of vaccines (e.g., Let’s get vaccinated because vaccines prevent infection) [ 25 , 26 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A message that targeted the fundamental motive of kin care significantly improved mothers’ attitudes toward HPV vaccination and significantly increased mothers’ intention to have their daughter(s) receive the HPV vaccine compared to a control message. Previous research and practice on behavior change, including vaccination recommendations, have been based mainly on cognitive behavioral models, and focused on cognitive beliefs such as perceived susceptibility and severity of infection [ 9 , 10 ]. Previous studies have shown that many vaccine recommendation messages target the fundamental motive of disease avoidance and communicate the causes of infectious diseases and the benefits of vaccines (e.g., Let’s get vaccinated because vaccines prevent infection) [ 25 , 26 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various models and theories have been used in studies of methods to encourage HPV vaccination, such as the health belief model, protection motivation theory, and theory of planned behavior [ 8 , 9 , 10 ]. These models and theories emphasize cognitive beliefs about health behaviors, such as perceived susceptibility of infection and perceived severity of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Befragung von 349 Ärztinnen und Ärzten in Italien zeigt, dass die HPV-Impfempfehlung besonders dann ausgesprochen wird, wenn die Ärzte und Ärztinnen selbst von der Sicherheit und Effektivität der Impfung überzeugt waren [22]. Dies bestätigt auch eine systematische Literaturübersicht mit Studien aus Frankreich [11]. Mögliche Hindernisse für das Aussprechen einer Impfempfehlung sind beispiels-weisediegeäußertenÄngste vonElternvor Nebenwirkungen der HPV-Impfung [11].…”
Section: Empfehlungsverhaltenunclassified
“…Dies bestätigt auch eine systematische Literaturübersicht mit Studien aus Frankreich [11]. Mögliche Hindernisse für das Aussprechen einer Impfempfehlung sind beispiels-weisediegeäußertenÄngste vonElternvor Nebenwirkungen der HPV-Impfung [11]. Opel et al (2013) verglichen verschiedene Empfehlungsstile miteinander: Der präsumtive Empfehlungsstil (präsumtiv: vermutlich, als wahrscheinlich angenommen) informiert Eltern darüber, dass Impfungen fällig sind ("Heute sind die Impfungen gegen HPV und Pertussis fällig", "Es ist Zeit für die jährliche Grippeimpfung"; [24]).…”
Section: Empfehlungsverhaltenunclassified
“…Various models and theories have been used in studies focused on encouraging vaccination, such as the health belief model, protection motivation theory, theory of planned behaviour and social cognitive theory 12–14…”
Section: Introductionmentioning
confidence: 99%